2011
DOI: 10.1016/j.cbpra.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Premature Termination in a Treatment for Generalized Anxiety Disorder

Abstract: In this paper we present a case of failure in an integrative treatment for generalized anxiety disorder (GAD) combining cognitive-behavioral therapy, an empirically supported treatment for GAD, and interpersonal-emotional processing therapy. The client of focus dropped out of treatment after the eighth session. Based on our analysis of this case, we discuss the participant, technical and relationship factors that were likely implicated in this case of premature termination in both of the cognitive-behavioral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The use of CBT interventions per se was not problematic; rather, it was the increased use of CBT interventions on the part of historically nondirective therapists who were facilitating relatively nondirective treatments, potentially illustrating the negative effects of breaking an established treatment frame. This has important implications for psychotherapy integration (Boswell, Llera, Newman, & Castonguay, 2011; Boswell & Goldfried, 2010). Although technical flexibility is an important element of being responsive (see Owen & Hilsenroth, 2014), there are also dangers to haphazard integration.…”
Section: Psychotherapy Process–outcomementioning
confidence: 99%
“…The use of CBT interventions per se was not problematic; rather, it was the increased use of CBT interventions on the part of historically nondirective therapists who were facilitating relatively nondirective treatments, potentially illustrating the negative effects of breaking an established treatment frame. This has important implications for psychotherapy integration (Boswell, Llera, Newman, & Castonguay, 2011; Boswell & Goldfried, 2010). Although technical flexibility is an important element of being responsive (see Owen & Hilsenroth, 2014), there are also dangers to haphazard integration.…”
Section: Psychotherapy Process–outcomementioning
confidence: 99%
“…Recent work on treatment failure among CBT for specific disorders suggested that some treatments may need to be refined so as to include research advances in areas such as memory and learning (Arch and Craske, 2011). It is reasonable to assert that patient, therapist, and dyadic-relational factors, as well as technical variables associated with the type of interventions chosen and their effective delivery, all combine to determine the treatment success or failure (Boswell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%